P380 Changes in faecal microbiome and metabolome are more pronounced in Crohn's disease patients who adhered to the CD-TREAT diet and responded by calprotectin. (30th January 2023) - Svolos, V; Hansen, R; Russell, R K; Gaya, D R; Seenan, J P; Macdonald, J; Wilson, D; Henderson, P; Din, S; Ho, G T; Quince, C; Ijaz, U Z; et al.
Abstract: Background: Treatment with the CD-TREAT solid food diet improves disease activity indices, faecal calprotectin (FCAL) levels and quality of life in adults and children with active Crohn's disease (CD); particularly in patients who adhere to the diet. Here we describe changes in faecal microbiome parameters during therapy with CD-TREAT and explore these changes against adherence. Methods: Children and adult patients with active CD completed an 8-week treatment with CD-TREAT. The levels of FCAL, pH, total sulphide (colorimetry), short chain fatty acids (SCFA), branched chain fatty acids (BCFA) (gas chromatography), total bacterial load (qPCR for total 16S rRNA gene copy number/g) were measured in baseline faecal samples and at four and eight weeks of CD-TREAT. Liquid chromatography mass spectrometry (LC-MS) faecal metabolomics and 16s rRNA sequencing of the faecal microbiome were performed at the same timepoints. Since CD-TREAT is gluten-free, detection of the gluten immunogenic peptide (GIP) in faeces was used as an objective biomarker of treatment adherence. Data are presented as median (IQR). Results: Forty patients [17 children, age: 14.0 (11.3-15.1) years; 23 adults, age: 33.9 (27.8-45.9) years] participated. Eighteen (45%) patients had detectable GIP in at least one of the two follow-up timepoints, suggesting incomplete adherence; the remaining 22 (55%) patients had undetectable GIP throughout the treatment course. Baseline FCAL levels decreased significantly in the group of patients with undetectable GIP [mg/kg, baseline: 1, 190 (3, 611-129); 8 weeks: 534 (92-1, 230), p<0.05] but not in patients with detectable GIP [mg/kg, baseline: 599 (328-1, 857); 8 weeks: 702 (278-1, 496)]. During CD-TREAT, the concentration of faecal acetate, propionate, butyrate, total sulphide, total microbial load and faecal pH significantly changed in those with undetectable GIP but were less pronounced where GIP was detectable (Figure 1). Shannon diversity and richness significantly increased at both genus and OTU level, the abundance of several taxa changed, and LC-MS faecal metabolome shifted during CD-TREAT, but only in those with undetectable GIP (Figures 2 & 3). Conclusion: We have identified that full adherence with CD-TREAT only occurs in 55% of recipients, however a significant reduction in calprotectin is seen in those who adhere, and this is associated with microbial and metabolic changes which parallel those seen in successful exclusive enteral nutrition.